Revascularisation for acute coronary syndromes: PCI or CABG? - Gunn, J; Taggart, D (2003)
Recent advances in both percutaneous coronary intervention and coronary artery bypass grafting emphasise the need for new randomised trials addressing acute coronary syndromes specifically, including a high proportion of patients with truly representative disease.